The Scarlet Convent: An Analysis of the Outcast Female Body in the Fictions of Nathaniel Hawthorne and Toni Morrison - Gbonegun, Olayinka Omololu (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2020)
This dissertation investigates how the female body is represented and defined in literature through instances of psychological transformation and/or exile, utilizing Julia Kristeva’s theory of abjection and the analysis of the outcast woman in modern society. To this end, this dissertation highlights the methods in which a community enforces traditionalism in regard to the human body through its close reading of the works of two prominent American writers: Nathaniel Hawthorne and Toni Morrison. Hawthorne’s 1850 novel The Scarlet Letter and Morrison’s 1997 novel Paradise. Setting their texts within two distinct time periods in American history, Hawthorne and Morrison employ different methods in order to present social conformity and social fear as well as their subsequent effects, shaping their female characters through the utilization of description, interaction, and written dialogue. By investigating the ways in which the women of these primary texts are written in relation to their own body through personal acknowledgement and gendered language, this dissertation seeks to highlight the nuances between the outcast woman and the exile, defining the female body’s place in the social sphere.
Keywords: Comparative Literature